PERAN AFIKSASI DALAM PENGAYAAN KOSAKATA CERITA ANAK BERBAHASA LAMPUNG - Alvindra, Alya Putri; Kurniawati, Kurniawati; Prayogi, Rahmat (STKIP Pesisir Selatan, 2025)
This study aims to examine the role of affixation in enriching the vocabulary of the Lampung language through an analysis of the children's literary work Anak Liman Sai Murah Hati by Nia Kartika Sari (2024). This study was motivated by the decline in the use of the Lampung language among the younger generation, which necessitates efforts to preserve regional languages through attractive and educational media such as children's stories. This study seeks to understand how the process of affixation contributes to the formation of new words and grammatical meanings that enrich the Lampung lexicon. The study uses a qualitative descriptive approach with text analysis methods. Data were obtained from bilingual children's story texts and explained through the stages of identification, classification, and interpretation of affixation forms, including prefixes, suffixes, and confixes. Data validity was maintained through triangulation analysis of theory and peer discussion to ensure accurate and contextual results. The results of the study show that the process of affixation in the Lampung language includes the use of prefixes (bu-, be-, te-, di-, je-), suffixes (-ni, -ku, -lah, -an), and confixes (ke-…-an, nge-…-ki, ku-…-ki). Each affix has a grammatical function while also strengthening the expressive and aesthetic value of literary texts. Affixation plays an important role in creating word form variations and enriching vocabulary relevant to the cultural context and the world of children.